The ability of Bipolaris sorokiniana isolated from spring barley leaves to survive in plant residuals of different crops - Dutbayev, Yerlan; Kharipzhanova, Aidana; Sultanova, Nadira; Dababat, Abdelfattah A.; Bekezhanova, Madina; Uspanov, Alibek (Science Publishing Group, 2022)
Spring barley is an important high-value crop globally. However, it is highly susceptible to soil-borne diseases in Kazakhstan and the world. Bipolaris sorokiniana (Sacc.) Shoemaker is the most important soil-borne pathogen that causes root rot and spot blotch diseases in cereal crops. This study aimed to evaluate the ability of B. sorokiniana isolated from spring barley leaves to survive in plant residuals of different crops. The fungus was isolated from spring barley leaves from the Zholbarys agro farm of Kerbylak district of Almaty, southeastern Kazakhstan, in 2021. Laboratory experiments were conducted at Kazakh National Agrarian Research University. The study was conducted on 10th days of seedlings of cereal, legume, and oilseed crops. The obtained results showed that seedlings of spring barley, spring wheat, and oats retained the B. sorokiniana infection. Interestingly, the infection of B. sorokiniana isolated from leaves of spring barley statistically significantly increased symptoms of spot blotch on spring wheat and spring barley seedlings, while symptoms decreased on oats (P-value <0.01). The introduction of rapeseed, chickpeas, peas, and oats into the crop rotation system in southeastern Kazakhstan could limit the volume of the B. sorokiniana infection in spring wheat and spring barley. On rapeseed, peas, and chickpeas seedlings no symptoms of spot blotch were observed (P-value <0.01).